What Happens in Pre-Marriage Counseling Rooms? Examining the Process of Pre-Marriage Counseling from the Perspective of Its Recipients - Karami , Banafsheh; Yousefi, Zahra (KMAN Counseling & Psychology Nexus, 2023)
The rising divorce rates and declining marriage rates have increasingly highlighted the necessity of pre-marriage counseling. The aim of the present study was to conduct a qualitative examination of the pre-marriage counseling process from the perspective of individuals who received such counseling in the city of Isfahan. This qualitative research was carried out using thematic analysis (Braun & Clarke, 2006). The study population consisted of individuals who had received pre-marriage counseling at counseling centers in Isfahan. The participants were purposively selected from those who had received pre-marriage counseling and had subsequently married based on that counseling. Data collection was conducted through semi-structured interviews containing questions related to the pre-marriage counseling experience. Qualitative data from the interviews were analyzed using Braun and Clarke's (2006) six-phase method. The results revealed that pre-marriage counseling comprises four main categories: assessment, education, advice, and conclusion, each containing subcategories, and these categories occur in a systematic process during counseling. Based on the findings, it can be concluded that although counselors may use different materials, tools, and methods in the pre-marriage counseling process, a specific pattern dominates the counseling process.